The Consumption of Ultra-Processed Foods Is Associated with Abdominal Obesity in Individuals on Hemodialysis in Brazil - Sara Jarske Gering; Cleodice Alves Martins; Nina Mara Paterlini Marques; Monica Cattafesta; Alexandre Cardoso da Cunha; Fabíola Lacerda Pires Soares; Edson Theodoro dos Santos Neto; Luciane Bresciani Salaroli (Obesities, 2024)
The consumption of ultra-processed foods is associated with abdominal obesity, but this association has not yet been investigated in individuals on hemodialysis. This cross-sectional study, developed with 1014 individuals, aimed to analyze the prevalence of abdominal obesity and its association with the consumption of ultra-processed foods in individuals on hemodialysis in Brazil. The consumption of ultra-processed foods was measured using a questionnaire, whose list of foods was based on the Surveillance System of Risk and Protective Factors for Chronic Non-Communicable Diseases through Telephone Enquiry. Waist circumference was used to determine the presence of abdominal obesity. The difference in proportions between the independent variables and the outcome was verified using Pearson’s chi-square test. Hierarchical logistic regression was used to determine the association between the outcome and the independent variables. The prevalence of abdominal obesity was 77.22%. In the final model, higher levels of consumption of ultra-processed foods, being male and an adult, having between 8 and 11 years of schooling, and practicing physical activity below the recommended level increased the chances of having abdominal obesity. This research provides a basis for the creation and improvement of public policies that promote improvements in these health determinants.